FIRST FINDS OF PERMIAN AMMONOIDS IN THE KOTEL'NYI ISLAND - Konstantinov A.G. (My University, 2001)
First ammonoid remains are found in the Lower Permian Munugudzhak Horizon, the northwestern coast of the Kotel'nyi Island (New Siberian Islands). They are used to define more precisely the age of host deposits and to clarify their palentological characteristics. Stratigraphic distribution of the distinguished ammonoid taxa and similar forms in the Permian sections of the Urals and Verkhoyansk region is analyzed. New paleontological data substantiate the Sakmarian Stage presence in the Permian System of the Kotel'nyi Island. Two ammonoid species Preshumardites bogoslovskyi Andrianov and Tabantalites etchiensis Andrianov are described.
Keywords: Permian; Sakmarian; Amonoid; New Siberian Islands; Kotel'nyi Island; Paleozoic::Permian; Палеозой::Пермская